Need analysis of holistic reading literacy teaching module integrating critical thinking and character - Dona, Rahma; Rahaimah Ali, Siti; Yulisinta, Florence; Ertika Latifah, Restiana (Institute of Advanced Engineering and Science, 2026)
The low levels of reading literacy and character development remain significant educational challenges among Indonesian students in the 21st century. Despite emphasizing higher-order thinking skills (HOTS) and character education in the national curriculum, elementary teachers struggle to effectively integrate these aspects into reading literacy teaching in the Bahasa Indonesia subject. This study identifies teachers’ challenges, difficult literacy topics, and the need for a structured module integrating HOTS and character. Using a design and development research (DDR) approach, an online survey of 287 grade 4 teachers from 171 elementary schools in Depok, West Java, was conducted. This study is the first to develop a grade-4-tailored holistic-HOTS-character (H2C) framework for reading literacy instruction, integrating cognitive, social, emotional, psychomotor, and moral elements. Additionally, teachers found independently retrieving and synthesizing information from multiple sources (22.30%) and teaching main ideas and supporting details (21.95%) to be the most challenging topics. Teachers strongly supported the development of an H2C teaching module (M=4.28 out of 5). The study also presents a visual H2C conceptual model to guide classroom implementation. This needs-analysis study confirms that teachers perceive a structured, holistic reading literacy teaching module as essential for enhancing student engagement, HOTS, and character development.